Alignment and political will: upscaling an Australian respectful relationships program. (29th May 2018) - Joyce, Andrew; Green, Celia; Kearney, Sarah; Leung, Loksee; Ollis, Debbie
Summary: Many small scale efficacious programs and interventions need to be 'scaled-up' in order to reach a larger population. Although it has been argued that interventions deemed suitable for upscaling need to have demonstrated effectiveness, be able to be implemented cost-effectively and be accepted by intended recipients, these factors alone are insufficient in explaining which programs are adopted more broadly. Upscaling research often identifies political will as a key factor in explaining whether programs are supported and up-scaled, but this research lacks any depth into how political will is formed and has not applied policy theories to understanding the upscaling process. This article uses a political science lens to examine the key factors in the upscaling process of a Respectful Relationships in Schools Program. Focus groups and interviews were conducted with project staff, managers and community organizations involved in the program. The results reveal how a key focusing event related to a highly profiled personal tragedy propelled family violence into the national spotlight. At the same time, the organization leading the respectful relationships program leveraged their networks to position the program within the education department which enabled the government to quickly respond to the issue. The study highlights that political will is not a stand-alone factor as depicted by up-scaling models, but rather is the end point of a complex process that involves many elements including the establishment of networks and aligned programs that can capitalize when opportunities arise.